HUMAN RESOURCES MANAGEMENT STRATEGY AND ITS ROLE TO IMPROVE LECTURER PERFORMANCE IN DEVELOPING ORGANIZATIONS - Khaeruman Khaeruman; Musa Hubeis; Nancy Yusnita (International Journal of Economy, Education and Entrepreneurship, 2023)
Human resource management plays an important role in improving lecturer performance and developing the organization. By taking the right steps in recruitment and selection, development and training, compensation, performance appraisal, and building an organizational culture that supports lecturer performance, organizations can create a conducive environment for lecturer development and growth as well as organizational progress. This research method uses a qualitative descriptive method using a literature review to find out effective human resource management strategies in improving lecturer performance to develop organizations. This method allows the author to obtain detailed and detailed data on effective strategies for improving lecturer performance. Thus, the results of this study can assist organizations in developing effective human resource management strategies in improving lecturer performance and developing the organization as a whole. The results of the research show that human resource management plays an important role in managing human resources which is one of the important assets in an organization. Human resources have different abilities, knowledge and skills, and if managed properly, human resources can be a major force in achieving organizational goals. Human resource management is an important factor in organizations. Human resource management can play an important role in improving lecturer performance in developing the organization by developing effective strategies to increase lecturer motivation, enthusiasm, will, and thoroughness